PEMAHAMAN INDIVIDU DAN MASALAH ANAK DALAM PROGRAM BIMBINGAN DAN KOSELING DI SEKOLAH - Muawanah, Elfi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
In general, the induvidual students, who has the problem, has been solved throughout the teachers’ oriented approach. The result of researches show that most of teachers applied punishment appoaches to identity the students who has the problem. It is recommed that the teachear should aplly other approaches such as Tatib ( or the role approach) and punishment approach, as the last alternative to solve the problem.Keyword: Pemahaman Individu, Masalah Individu, Pemdekatan Tatib dan Pendekatan Punishment